Carrageenan characteristics of Kappaphycus alvarezii from various harvest ages. Issue 1 (October 2021) - Firdaus, Muhamad; Nurdiani, Rahmi; Awaludin Prihanto, Asep; Puji Lestari, Eka; Suyono,; Amam, Faizul
Abstract: The age of harvest can influence the properties of carrageenan Kappaphycus alvarezii . The difference in the growth of the thallus allows the carrageenan content in it to be different. This study aims to preserve the properties of carrageenan K. alvarezii from different harvest ages. The method used is experimental. K. alvarezii were harvested three replicates at 30, 45 and 60 days of age. The procedures of carrageenan flour production were dried, washed, extracted with KOH, rinsed, extracted with water, filtered, soaked in KCl, neutralized, dried, pulverized, and sieved. The parameters were yield, moisture content, total ash content, acid insoluble ash content, sulfate content, viscosity and gel strength. The results showed that carrageenan from different harvest ages yields between 16.8-36.11%, moisture content 9.85-11.57%, total ash content 25.79-31.27%, acid-insoluble ash content 0.29-0.52%, had a sulfate content of 14.27-20.34%, a viscosity of 28-64.66 cP and a gel strength of 7.8-10.03 N / cm², the character of this product still conforming to the established FAO standards. The conclusion is that carrageenan harvested from seaweed at 45 days of age has properties close to FAO standards, with an average yield of 27.11%, 9.85% moisture content, 31.27% total ash content, 0.29% acid-insoluble ash content, sulfate content of 20.13%, viscosity of 28 cP and gel strength of 7.8 N / cm².